Segmentation, Targeting and Positioning of The Tourism Industry before, during The Covid-19 Pandemic and After for The Tourism Industry in Indonesia - Hidayat, Candra; Zeng, Yi (Jurnal Penelitian Pariwisata, 2023)
This research aims to observingtourism businesspre, during and post Covid-19 pandemic. Evaluating and selecting market segment, firstly the highest foreign tourist arrivals to Indonesia by nationality is Malaysia, Timor-Leste, Singapore, China and Australia. Secondly, foreign tourist arrivals to Indonesia by gender male tourist bigger than female tourist is Malaysia, Timor-Leste, Singapore, India, Japan, America, England and South Korea. In reverse, female tourist bigger than male tourist is China and Australia. Thirdly, foreign tourist arrivals to Indonesia by age Generation Y and Generation Z is Malaysia, Timor-Leste, China, India, Japan, America, England, South Korea and Australia. Equal between baby boomers and generation X, Generation Y and Generation Z is Singapore. Fourthly, international tourists spending more than $ 1000 are Singapore, China, India, Japan, America, England, South Korea and Australia. Afterwards, international tourists spending less than $ 1000 are Malaysia and Timor-Leste. Fifthly, international tourists arrivals by main purpose of visit for vacation more than 78 percent is Malaysia, Timor-Leste, China, Singapore, Australia, India, Japan, America, England and South Korea. Positioning strategies as a needs and wants from tourists and communicating and delivering the products. Indonesia needs in making appropriate strategy for more appealing and visible, through segmenting, targeting and positioning. Keywords: Segmentation, Targeting, Positioning